An integrative approach to assessing the pathogenic potential of Escherichia coli strains isolated from urine - Mariia A. Makarova; Zoya N. Matveeva; Lidiya A. Kaftyreva (Журнал микробиологии, эпидемиологии и иммунобиологии, 2024)
Introduction. Uropathogenic Escherichia coli (UPEC) are characterized by the ability to survive and reproduce in the urinary tract due to the presence of specific virulence factors. In routine laboratory practice, the detection of diagnostically significant bacteriuria does not provide an idea of the level of infection of the urinary system (renal parenchyma, bladder), the pathogenic potential of the strain in the progression and chronicity of the infectious process, and the occurrence of life-threatening conditions (urosepsis, meningitis).